The Role and Authority of Class I Auctioneers in Indonesia within the Framework of State Administrative Law - Br. Turnip, Lydia Fransiscani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study analyzes the position and authority of Class I Auction Officials in Indonesia from the perspective of state administrative law. The research finds that the legal basis for the position and authority of Class I Auction Officials is a ministerial regulation, not a law, which contradicts the legal requirements for authentic deeds as stipulated in Article 1868 of the Civil Code. The current system grants the Ministry of Finance the dual role of regulator and executor of auctions, which raises concerns about independence and neutrality. This dual role can lead to legal uncertainty because the official's authority is based on ministerial delegation rather than attribution from a higher law. The ideal arrangement, from a state administrative law perspective, would be to establish a clear legal framework at the level of a law (undang-undang) to regulate the position, authority, and recruitment of Class I Auction Officials. This would ensure their independence and neutrality. It is suggested that the role of auction officials be given to professionals outside the civil service, while the Ministry of Finance should act as a supervisor to prevent conflicts of interest and ensure a fair and just auction process. This would align the Indonesian auction system with the principles of good governance and legal certainty.